Proceedings of the Third International Conference on Advances in Computing Research (ACR’25) - Daimi, Kevin; Al Sadoon, Abeer (Lecture Notes in Networks and Systems, 2025)
XIX, 520 p. 121 illus., 97 illus. in color.